PERAN ORANG TUA DALAM MENGEMBANGKAN KEMANDIRIAN BELAJAR ANAK DI RUMAH SELAMA PANDEMI COVID-19 - Rini Loisa Tasidjawa; Willem Hetharion; Yohana Touwe (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2021)
This study aims to determine the role of parents in developing children's learning independence at home during the COVID-19 pandemic in Skikilale Village, Waplau District, Buru Regency. The research method used is a qualitative method with data collection through observation, interviews, and documentation with descriptive data analysis. Data analysis techniques consist of data reduction, data presentation, and concluding. The results showed that the role of parents in developing children's learning independence at home is the most important process in directing, guiding, petrifying, and providing facilities for children to be able to form independent personalities by themselves because according to parents, children must be accustomed to being more independent in the learning process so that Children know their abilities. The role of parents in developing children's learning independence at home during the COVID-19 pandemic in educating children includes mentoring and as a motivator.Â Keywords: Role of Parents, Children's Learning Independence, Covid 19 Pandemic